Explaining Inflation Persistence by a Time-Varying Taylor Rule - Christian Conrad; Thomas A. Eife (University of Heidelberg, Department of Economics, 2010)
In a simple New Keynesian model, we derive a closed form solution for the inflation persistence parameter as a function of the policy weights in the central bank's Taylor rule. By estimating the time-varying weights that the FED attaches to inflation and the output gap, we show that the empirically observed changes in U.S. inflation persistence during the period 1975 to 2010 can be well explained by changes in the conduct of monetary policy. Our findings are in line with Benati's (2008) view that inflation persistence should not be considered a structural parameter in the sense of Lucas.
urn:nbn:de:bsz:16-opus-110433
Keywords: 330; inflation persistence; Great Moderation; monetary policy; New Keynesian model; Taylor rule; Inflation; Hysterese; Geldpolitik; Taylor-Regel; Neoklassische Synthese; Schätzung; USA